2003
DOI: 10.1002/cm.10090
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of desmin mutations on cytoskeletal and cellular integrity in cardiac myocytes

Abstract: Mutations in desmin have been associated with a subset of human myopathies. Symptoms typically appear in the second to third decades of life, but in the most severe cases can manifest themselves earlier. How desmin mutations lead to aberrant muscle function, however, remains poorly defined. We created a series of four mutations in rat desmin and tested their in vitro filament assembly properties. RDM-G, a chimera between desmin and green fluorescent protein, formed protofilament-like structures in vitro. RDM-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 66 publications
2
7
0
Order By: Relevance
“…Nevertheless, all desmin mutants revealing defective assembly properties were dominant because, in 1:1 mixtures with WT desmin, they led to aberrant assembly as demonstrated by viscometry and cDNA-transfection into vimentin-containing 3T3 fibroblasts (data not shown). Consistent with these data, the disruption of the desmin cytoskeleton in cultured rat neonatal cardiac myocytes by overexpression of an engineered desmin mutant with an arginine to cysteine change in coil 1B has demonstrated that also in an authentic desmin environment such mutants exhibit a dominant effect (34).…”
Section: Discussionsupporting
confidence: 64%
“…Nevertheless, all desmin mutants revealing defective assembly properties were dominant because, in 1:1 mixtures with WT desmin, they led to aberrant assembly as demonstrated by viscometry and cDNA-transfection into vimentin-containing 3T3 fibroblasts (data not shown). Consistent with these data, the disruption of the desmin cytoskeleton in cultured rat neonatal cardiac myocytes by overexpression of an engineered desmin mutant with an arginine to cysteine change in coil 1B has demonstrated that also in an authentic desmin environment such mutants exhibit a dominant effect (34).…”
Section: Discussionsupporting
confidence: 64%
“…Desmin mutations have been linked to both dilated (482,584) and restrictive cardiomyopathies (20,712,930). Gene transfer of mutated desmin into neonatal cardiac myocytes disrupted the sarcomeric banding pattern (341). These studies demonstrate that alterations in desmin filament assembly have a dominant effect on cellular sarcomeric assembly, an observation consistent with the dominant mode of inheritance that characterizes desminrelated cardiomyopathies.…”
Section: B Intermediate Filaments (Desmin)supporting
confidence: 54%
“…The de novo nature of the mutation in our patient is strong evidence that it is disease-causing, and we have also found that the mutant GFAP fails to polymerize normally in transiently transfected cells, and is dominant to the wild type. These polymerization properties of the extended, mutant GFAP add further caution to the use of C-terminal tags of intermediate filament proteins (Haubold et al, 2003). …”
Section: Discussionmentioning
confidence: 99%